Decentralized Formation Control of a Swarm of Quadrotor Helicopters - (:unkn) unknown (IEEE Computer Society, 2019)
We propose a decentralized hybrid swarm control mechanism for quadrotor helicopters. The mechanism includes formation, rotation, tracking, and inter-agent collision avoidance capabilities. We provide stability analysis of the proposed rule assuming that each quadrotor has a single-integrator dynamics on the formation and tracking level. Then we integrate the formation level control inputs to obtain the desired position of the quadrotors and design the low level individual quadrotor controllers to track these positions. Since the output of each decentralized swarm controller is a desired location for a member, the quadrotors are required to have position controllers in addition to attitude controllers. Both simulation and real world experiments show that a group of quadrotor agents successfully achieves desired formation, rotation, and tracking predefined way-points without any collisions. © 2019 IEEE.
Keywords: consensus; decentralized hybrid control; formation control; quadrotor; Swarm; swarm control; UAV